2019
DOI: 10.3390/toxins11110676
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for a Satisfactory Treatment Outcome with Intravesical Botulinum Toxin A Injection in Patients with Interstitial Cystitis/Bladder Pain Syndrome

Abstract: A botulinum toxin A (BoNT-A) intravesical injection can improve the symptoms of interstitial cystitis/bladder pain syndrome (IC/BPS). Patients with IC/BPS have different clinical characteristics, urodynamic features, and cystoscopic findings. This study assessed the treatment outcomes of a BoNT-A intravesical injection and aimed to identify the predictive factors of a satisfactory outcome. This retrospective study included IC/BPS patients treated with 100 U BoNT-A. The treatment outcomes were assessed by globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Furthermore, it also inspires us that the treatment outcome could somehow depend on the disease duration in BPS/IC patients. For example, the treatment outcomes of botulinum toxin A are different between IC/BPS patients with different disease duration [25]. The main limitation of our present study is that we only focus on the Notch1 receptor in Notch1 signaling without involving the ligands of Notch1 signaling, including Jagged and Delta.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, it also inspires us that the treatment outcome could somehow depend on the disease duration in BPS/IC patients. For example, the treatment outcomes of botulinum toxin A are different between IC/BPS patients with different disease duration [25]. The main limitation of our present study is that we only focus on the Notch1 receptor in Notch1 signaling without involving the ligands of Notch1 signaling, including Jagged and Delta.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it also inspires us that the treatment outcome could somehow depend on the disease duration in BPS/IC patients. For example, the treatment outcomes of botulinum toxin A are different between IC/BPS patients with different disease duration [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…All patients were informed of the possible complications associated with intravesical PRP injection, such as hematuria, micturition pain, difficult urination, transient urinary retention, or urinary tract infections (UTIs). Treatment outcomes were assessed using the GRA at 3 and 6 months after the first PRP injection ( Wang et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…BoNT-A can relieve pain, urgency, and frequency for refractory IC/BPS and improve the functional bladder capacity [ 198 , 199 ]. Kuo et al suggested that functional bladder capacity (136 ± 79.1 vs. 208 ± 110, p = 0.000) was significant improvement after four repeated injections with BONT- A in IC/BPS patients.…”
Section: Impact Of Potential Biomarkers For Assessment Of Ic/bps Therapeutic Outcomementioning
confidence: 99%